Perspectives on Terrorism, Culture, and Globalization: A Comprehensive Review of the Contemporary Scholarship - Ivanova, Aleksandra G.; Burganova, Inna N.; Sheshukova, Galina V. (Journal of History Culture and Art Research, 2020)
There have been continuous debates on the influence of globalization and cultural interactions on the origins and spread of terrorism, Hence, there are numerous attempts to analyze the underlying causal mechanism between these concepts. Given the interdisciplinary nature of the already established body of knowledge, the paper provides a detailed review of the contemporary scholarship on such diverse concepts as “globalization,” “culture,” and “terrorism.” The goal is to systemize the existing approaches used by researchers to analyze the interconnectedness of globalization, culture, and terrorism and present a holistic picture of the current state-of-the-art (which could be used to identify potentials for future research). Relying on the data available from the Scopus abstract and citation database, the paper covers the period from 1998 to 2019. First of all, the paper analyzed a number of quantitative indicators, such as an overall number of papers published, their document types, the leading countries in terms of the scholarly output, and the biggest subject areas. Second, the authors select a total of 40 research papers from the database and conduct a detailed review, the purpose of which is to present a holistic view on the key perspectives developed to analyze such concepts as “globalization,” “culture,” and “terrorism.” The review clearly demonstrates that one could identify the total of five distinct perspectives in the contemporary scholarship: (1) “Postcolonialism,” (2) “Religion and Identity Studies,” (3) “Social Science Approaches,” (4) “Education and Culture,” and (5) “Popular Culture and Mass Media.” The paper provides a summary of each approach, with a detailed account of the relevant papers. Thus, the review presents unique insights into how the current body of knowledge on the concepts “globalization,” “culture,” and “terrorism” is organized, highlighting the critical and well-established research avenues (at least how they are reflected in one of the leading abstract and citation database).